Awareness issue of Montgomery watt about the Muhammadan prophecy: a critical and analytical study - Al-sansei, Nagi Ali (Journal of Islamic Sciences, 2019)
This study belongs to the Islamic ideological studies fighting for Islam and its prophet against the doubts of Orientals and their illogical interpretation of different subjects is the prophecy revealed to Muhammad peace be upon him by the angel Gabriel. Its sheds light on the Oriental William Montgomery s issue of the study and interpretation for the examples and away the prophet Muhammadan PBH got revealed from God. Based on the modern oriental resources that interpreted the Muhammad an prophecy with the poetic Muse, magic, astrology, Puritanism, and so on and applying philosophical theories like; the modern spiritualism, creative imagination, psychoanalysis theories like; unconsciousness theory and collective unconsciousness and several other theories that never belong to religious dogmatic studies and theology which are private in each religion. the Study explained the close and far cognitive of Montgomery' s study of the Muhammad an prophecy based on these theories and interpretation in order to set Muhammad as a non- repetitive divine selection, person and subjects, resulted in Holy Quran, the world of God which is never ever fake and it's the resource for the worship rituals rules and legislative too, shifted to spoken phenomenon made by the collective unconscious mid of Muhammadan PBH. Watt's interpretations got to equal the Quran with the other texts in order to pave the ground take off the Quran's sacredness and its God source, doubting this source and dealing with it as a human text subjected to the philosophical and literary theories and the curricula of languages, philosophy, sociology and psychology as well.
Keywords: Montgomery Watt; Divine Revelation; Prophecy of Muhammad; PBUH; Orientalism